Mastering orthopedic techniques intra-articular fractures - Malhotra, Rajesh (India : Jaypee, 2013)
Mastering Orthopedic Techniques series, this comprehensive manual is a complete guide to the surgical management of intra-articular fractures. Beginning with an introduction providing an overview of articular fractures, the following chapters provide a 'how to' style commentary, joint by joint and by fracture type.
Contents 1. Intra-articular Fractures: What have we learnt? 2. Glenoid Fractures 3. Proximal Humeral Fractures: Open Reduction and Internal Fixation 4. Hemiarthroplasty for Acute Proximal Humerus Fractures 5. Reverse Shoulder Arthroplasty for Proximal Humeral Fractures and more others...
Incluye índice y título en inglés
Incluye bibliografía en inglés
Keywords: ORTOPEDIA; lembs; ORTOPEDIA -ENFERMEDADES